Species Diversity and Nesting Descriptions of Stingless Bees (Apidae; Meliponini) on Ambon Island - Lamerkabel, Jacobus S A; Rumthe, Ria Y; Sarkol, Marsia E (JURNAL BUDIDAYA PERTANIAN, 2023)
Stingless bees have an important role, namely as a potential pollinator for increasing the production of various plants, as well as producing honey and propolis. This study aims to obtain species diversity, morphological characters, morphometric characteristics of stingless bees and descriptions of types of nesting stingers. It was carried out from March to May 2021. Observations of the morphological characters of the worker strata included: body color, thorax, mesoscutum, mesoscutellum, propodeum, abdomen, forewing color, number of hammuli, posterior hair of the back tibia, and elliptical disc on the inside of the back basitarsus. While the morphometric strata of workers measured were: body length, head width, head length, eye width, malar space length, second flagellomere width, long wingspan and tegula, back tibia width, back basitarsus width. Observations of stingless beehives include: hive height, nest location/material, entry length and diameter, entrance color and texture. The results of the study of the stingless bee species found in Leihitu District were T. clypearis, and in Salahutu District were T. clypearis and T. fuscobalteata. The morphological character of the species of T. clypearis is the body has a brownish black color with a size of 3.36-3.56 mm, the belly color is blackish brown. Species T. fuscobalteata dominant body brownish black with a body size of 2.78-3.24 mm brownish yellow belly color. Description of the nest of T. clypearis species, namely: nest height 26-219 cm, entrance brown and black, hard and soft structure, entrance hole length 0.3-7 cm, diameter 0.3-4 cm. Types of nesting T. fuscobalteata were: nesting height 160-193 cm, entrance brown, hard and soft structure, entrance length 0.8-1.3 cm, diameter 0.3-1.2 cm. With nesting substrates namely wood, stone and iron.